Islamic Philanthropy in Healthcare in South Asia: Lessons from Sri Lanka and Nepal - Salieu Jallow, Mamadou; Ilmaskal, Radian; Verdinando, Rino (MD Research Center Yogyakarta, 2025)
This study examines the potential of Islamic philanthropic instruments, zakat, waqf, and sadaqah in improving healthcare access in Sri Lanka and Nepal, two non-Muslim majority South Asian nations with fragmented health systems. Employing a traditional qualitative literature review, the research analyses academic and grey literature to explore how these faith-based resources can supplement public health financing. The findings reveal that Islamic philanthropy provides crucial funding for facilities, community programs, and subsidised care, particularly in underserved regions. However, its effectiveness is mediated by significant challenges, including regulatory misalignment, operational capacity constraints within philanthropic institutions, and the need for cultural sensitivity in implementation. The study further highlights the catalytic role of digital technology in enhancing transparency and donor engagement, and underscores the necessity of strategic multi-stakeholder collaboration between philanthropic entities, government agencies, and international health bodies. In conclusion, while Islamic philanthropy holds substantial promise for health system strengthening, realising its full potential requires context-adaptive governance frameworks, robust accountability mechanisms, and inclusive partnerships that respect local socio-cultural dynamics. This integrated approach is vital for leveraging Islamic philanthropy towards more equitable and resilient healthcare delivery in both countries.